Emphasizing access to health and treatment services in order to identify the key factors influencing an age-friendly city - Komasi, Hossein; Hashemkhani Zolfani, Sarfaraz; Antuchevičienė, Jurgita (International Journal of Strategic Property Management, 2023)
One of the most important goals of urban management is to provide comfort and well-being for all citizens. According to the population trend of the world, a massive segment of the future population will be the elderly. Therefore, it is crucial to pay attention to the needs of this segment of society. In this regard, the concept of an age-friendly city that provides a favorable urban environment for the elderly has entered the world’s scientific literature. Because one of the essential land utilization that the elderly have a lot of connection with is health-therapeutic use, the current research has been carried out to evaluate the current health-treatment situation of Songhor city in terms of its usefulness for the elderly. In the second step, the most important drivers influencing the location of these uses have been identified from the perspective of related experts. This research is applied in terms of purpose and descriptive-analytical in terms of research method. The required data has been collected using library-documentary studies, field surveys, and the distribution of questionnaires from related experts. According to the study’s findings, more than 60% of treatment facilities in Songhor city are inaccessible to the elderly. This difficulty varies by therapeutic use; in some cases, it is less difficult than the average, while in others, it is more difficult. In addition, three factors–investment cost (V3), rivalry (V10), and population density (V8)–have been identified as the age-friendly city’s main drivers out of a total of 18 main variables. The study’s findings indicate that the global population is aging, and urban managers and officials should design urban environments following the requirements of the projected population by putting forth medium- and long-term plans.